Vision impairment and traffic safety outcomes in low-income and middle-income countries: a systematic review and meta-analysis. Issue 10 (October 2021) - Piyasena, Prabhath; Olvera-Herrera, Victoria Odette; Chan, Ving Fai; Clarke, Mike; Wright, David M; MacKenzie, Graeme; Virgili, Gianni; Congdon, Nathan
Summary: Background: Road traffic injuries are a major public health concern and their prevention requires concerted efforts. We aimed to systematically analyse the current evidence to establish whether any aspects of vision, and particularly interventions to improve vision function, are associated with traffic safety outcomes in low-income and middle-income countries (LMICs). Methods: We did a systematic review and meta-analysis to assess the association between poor vision and traffic safety outcomes. We searched MEDLINE, Embase, PsycINFO, CINAHL, Web of Science, Cochrane Database of Systematic Reviews, and the Cochrane Central Register of Controlled Trials in the Cochrane Library from database inception to April 2, 2020. We included any interventional or observational studies assessing whether vision is associated with traffic safety outcomes, studies describing prevalence of poor vision among drivers, and adherence to licensure regulations. We excluded studies done in high-income countries. We did a meta-analysis to explore the associations between vision function and traffic safety outcomes and a narrative synthesis to describe the prevalence of vision disorders and adherence to licensure requirements. We used random-effects models with residual maximum likelihood method. The systematic review protocol was registered on PROSPERO, CRD-42020180505. Findings: We identified 49 (1·8%) eligible articles of 2653 assessed and included 29 (59·2%) in the various data syntheses. 15 394 participants (mean sample size n=530 [SD 824]; mean age of 39·3 years [SD 9·65]; 1167 [7·6%] of 15 279 female) were included. The prevalence of vision impairment among road users ranged from 1·2% to 26·4% (26 studies), colour vision defects from 0·5% to 17·1% (15 studies), and visual field defects from 2·0% to 37·3% (ten studies). A substantial proportion (range 10·6–85·4%) received licences without undergoing mandatory vision testing. The meta-analysis revealed a 46% greater risk of having a road traffic crash among those with central acuity visual impairment (risk ratio [RR] 1·46 [95% CI 1·20–1·78]; p=0·0002, 13 studies) and a greater risk among those with defects in colour vision (RR 1·36 [1·01–1·82]; p=0·041, seven studies) or the visual field (RR 1·36 [1·25–1·48]; p<0·0001, seven studies). The I 2 value for overall statistical heterogeneity was 63·4%. Interpretation: This systematic review shows a positive association between vision impairment and traffic crashes in LMICs. Our findings provide support for mandatory vision function assessment before issuing a driving licence. Funding: None.